Shiitake mushroom-induced flagellate dermatitis: Case report - Abdullah Aleisa; Natalia Plotnikova (Wolters Kluwer Medknow Publications, 2020)
Shiitake mushroom (SM)-induced flagellate dermatitis follows the ingestion of undercooked SMs. Pathogenesis is thought to be a delayed-type hypersensitivity reaction to lentinan, a heat-sensitive polysaccharide found in SM. Eruption is self-resolving and lasts from 2 days to 6 weeks. It presents as pruritic, linear, whiplash-like, erythematous plaques on the trunk. Flagellate eruption differential diagnoses include bleomycin-induced dermatitis, dermatomyositis, and adult-onset Still's disease.